The Paradiplomacy of the Cities. A Strategy of Urban Development - Zeraoui, Zidane; Rey, Fernando (Revista del CLAD Reforma y Democracia, 2016)
This article on paradiplomacy of the city, focuses primarily to define conceptually the international policy of subnational actors, and in this specific case, the cities. The second part of the paper is centered on the city branding not only as an economic tool but as a central element of urban development. Several examples of urban practices as London or Geneva, has shown that cooperation between cities and a comprehensive approach to long-term development, are the key elements for urban sustainability.